(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Fractures in children aged under five years constitute a priority concern owing to their distinctive epidemiological features and the differential diagnosis between accidental and non-accidental injury. This meta-analysis pools evidence from seven seminal epidemiological studies published between 1983 and 2024, including retrospective cohorts, national registries, insurance claims databases, and systematic reviews, to clarify the incidence, anatomical location, and mechanisms of pediatric fractures. The review finds that the incidence of fracture is comparatively low among non-ambulant infants aged less than 12 months but rises dramatically with the commencement of independent ambulation, with the distal forearm, tibia, and clavicle being predominantly affected while in our study Falls from low heights are the major injury mechanism among ambulant toddlers, whereas a high percentage of fractures among infants aged less than one year are due to non-accidental reasons where Methodological diversity among studies restricts quantitative pooling, highlighting the necessity for harmonized prospective studies and finally The review offers crucial information for clinicians in discerning normative fracture patterns from those raising suspicion of abuse, as well as for public health specialists implementing targeted prevention initiatives. Standardized data collection and prospective study designs should be prioritized in future research to further delineate fracture risk factors and enhance child safety outcomes.